2009
DOI: 10.1590/s1806-37132009001100002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de asma em adolescentes na cidade de Fortaleza, CE

Abstract: Objective: To determine the prevalence of asthma among adolescents (13-14 years of age) in the city of Fortaleza, Brazil. Methods: This was a cross-sectional study involving 3,015 adolescents at public and private schools between 2006 and 2007. The participants completed the International Study of Asthma and Allergies in Childhood questionnaire. Results: The prevalences of "wheezing ever", "wheezing within the last 12 months" (active asthma) and "asthma ever" (physician-diagnosed asthma) were 44.1%, 22.6% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
4
0
4
Order By: Relevance
“…[11] However, in general it was found that prevalence rate is more in the United Kingdom, Canada, Australia, New Zealand, Brazil, and other developed countries, ranging from 15% to 20%. [11617] A very high prevalence of history of wheezing was found in three studies in Costa Rica with 46.8%, 42.9%, and 45.1% in different age groups conducted among school children. [18] In contrast to this, it was shown by an Indian study that prevalence of asthma among adults aged ≥15 years is 2.05%.…”
Section: Discussionmentioning
confidence: 99%
“…[11] However, in general it was found that prevalence rate is more in the United Kingdom, Canada, Australia, New Zealand, Brazil, and other developed countries, ranging from 15% to 20%. [11617] A very high prevalence of history of wheezing was found in three studies in Costa Rica with 46.8%, 42.9%, and 45.1% in different age groups conducted among school children. [18] In contrast to this, it was shown by an Indian study that prevalence of asthma among adults aged ≥15 years is 2.05%.…”
Section: Discussionmentioning
confidence: 99%
“…( 22 ) A previous study found that, as the degree of morbidity decreased, the number of adolescents who did not categorize themselves as having asthma increased. ( 14 ) In contrast, the increase in physician-diagnosed asthma observed in our second survey indicates better recognition of the problem by this population or even increased acceptance of the term "asthma", which contributes to more cases being treated. Corroborating this possibility, our more recent survey showed that the prevalences of the various degrees of asthma severity remained stable, although the prevalences of other symptoms increased.…”
Section: Discussionmentioning
confidence: 54%
“…Therefore, the objective of the present study was to determine the prevalences of asthma and rhinitis in adolescents (13-14 years of age) in the city of Fortaleza, Brazil, in 2010, comparing the results with those obtained in another prevalence survey conducted in 2006-2007. ( 13 , 14 ) …”
Section: Introductionmentioning
confidence: 99%
“…Uma das hipóte-ses para justificar este predomínio seriam o menor diâmetro e maior tônus das vias aéreas, com menores fluxos pulmonares durante o primeiro ano de vida mais evidente em meninos do que em meninas, ocorrendo uma reversão a partir da puberdade. 16 No estudo de CASAGRANDE et al 13 , embora tenha sido verificada uma predominância de 50,6% dos participantes de seu estudo classificados como sexo feminino, após análise estatística foi encontrado um risco de 2,4 vezes maior para asma no sexo masculino.…”
Section: Discussionunclassified